Kemanusiaan dalam Kumpulan Cerpen Dua Tengkorak Kepala: Cerpen Pilihan Kompas 2000 - Aditiawarman, Aditiawarman; Adek, Muhammad (Persona: Kajian Bahasa dan Sastra, 2024)
This study aims to explore the types and forms of human values in the short story collection Dua Tengkorak Kepala from Cerpen Pilihan Kompas: 2000. Using the sociology of literature theory, this qualitative research employs a descriptive method. The Dua Tengkorak Kepala collection serves as the data source for this research. Data collection methods include reading and comprehending the stories in Dua Tengkorak Kepala, identifying and recording elements related to human values in the stories, and identifying events that reflect human values. The validation technique used in this research is triangulation. Data analysis techniques involve classifying data based on the speech/actions or thoughts of characters and narrators that relate to human values, analyzing/interpreting the data, summarizing the analysis results, and writing the report. The results of this study are: (1) Types of human values. Human values are categorized into four parts: (a) Human and God, (b) Human and Nature, (c) Human and Others, and (d) Human and Self; (2) Forms of human values, categorized into five parts: (a) Value of Truth, (b) Value of Peace, (c) Value of Compassion, (d) Value of Righteous Behavior, and (e) Value of Nonviolence.